Psychological and Environmental Correlates of HPA Axis Functioning in Parentally Bereaved Children: Preliminary Findings. Issue 2 (22nd March 2013) - Kaplow, Julie B.; Shapiro, Danielle N.; Wardecker, Britney M.; Howell, Kathryn H.; Abelson, James L.; Worthman, Carol M.; Prossin, Alan R.
<x xml:space="preserve">Abstract</x> This study examined bereaved children's HPA‐axis functioning (cortisol awakening response; CAR) in relation to psychological distress, coping, and surviving parents' grief reactions. Participants included 38 children (20 girls) with recent parental loss (previous 6 months) and 28 of their surviving caregivers (23 women) who were assessed using self‐report instruments and in‐person, semistructured interviews. Interviews involved discussions about the child's thoughts and feelings related to the loss. Participants provided 3 saliva samples at home (awakening, 30 minutes later, and evening) over 3 successive days, beginning on the day following the interview. Results show a significant relation between dampening of the child's Day 1 CAR and more symptoms of anxiety (r = −.45), depression (r = −.40), posttraumatic stress (r = −.45), and maladaptive grief (r = −.43), as well as higher levels of avoidant coping (r = −.53). Higher levels of parental maladaptive grief were also associated (r = −.47) with a dampening of the child's Day 1 CAR. Our results raise the possibility that blunted CAR may be a result of accumulating allostatic load and/or a result of emotionally challenging events (discussions regarding the deceased) and their subsequent processing (or lack thereof) within the family, which may be particularly stressful for those bereaved children experiencing high levels of psychological distress, avoidant coping, and parental maladaptive grief.